Continuous ultrasonic-mediated solvent extraction of lactic acid from fermentation broths. (1st March 2017) - Hu, Yunzi; Kwan, Tsz Him; Daoud, Walid A.; Lin, Carol Sze Ki
Abstract: A novel method of lactic acid recovery from fermentation broths by continuous ultrasonic solvent extraction is disclosed in this study. Fermentation broths from defined medium, mixed food waste hydrolysate and bakery waste hydrolysate were employed. Ultrasonication was applied to improve the extraction efficiency combined with ethyl acetate optimum solvent to replace conventional amine-based complex systems. The optimization process was performed by investigation of various conditions, in which initial lactic acid concentration range of 350–400 g L −1 extracted into ethyl acetate (1:2 v/v) by sonication at pH 2 under room temperature was suggested. Lactic acid was successfully recovered with a concentration of 400–500 g L −1, at overall yields of 82–84%, and purity around 98%, showing the high effectiveness of this new method. The simple and effective recycling of the solvent confirms the method in a green and sustainable manner. Graphical abstract: Highlights: Lactic acid recovery from fermentation broth by ultrasonic extraction was conducted. Lactic acid was recovered at overall yields of 82–84% and of purity over 98%. Energy consumption by sonication was 0.03 kWh per kg of lactic acid recovered. Ultrasonic extraction was effective in liquid-liquid extraction of organic acids.